A Sustainable Environmentally Friendly Pre-Treatment Process towards Knit-Dyeing Technology Convenient for Environmental Perspective. Issue 1 (December 2020) - Dutta, P; Sufian, M A; Sheen, Sh M; Chowdhury, S
Abstract: The use of enzymes in textile processing has made a major contribution to the development of textiles, in particular, textile wet processing. With temperatures of 95°C, a method of conventional scouring on cotton knitted fabric is conducted in a higher base medium (pH 10.5-12) with sodium hydroxide. This process is gradually being replaced by an eco-friendly and economical approach using enzymes that obviate the non-cellulosic impurities. In this work, cotton knit fabric samples were bio-scoured by BioPrep® Fusion (bio-scouring enzyme) and also, they were scoured by using the traditional method. Then, the physicochemical parameters of the effluents derived from the scouring process have been investigated in this study. The physical parameters include Electrical Conductivity (EC), Total Solids (TS), Total Suspended Solids (TSS), and Total Dissolved Solids (TDS). Moreover, the chemical parameters involve pH, Biochemical Oxygen Demand (BOD), Dissolved Oxygen (DO), Chemical Oxygen Demand (COD), and Alkalinity. Furthermore, the impacts of traditional caustic soda scouring on environmental contamination have also been investigated using a number of different techniques and apparatus and compared to that of enzymatic scoured fabrics. The results of the physicochemical parameters of the effluents test reveal greater ecological developments in the use of the enzyme. Based on the findings of this analysis, it is often understood that the bio-scouring process performed far better as opposed to the traditional method, and also the method is environmentally friendly and sustainable. Hence, enzymatic scouring can be utilized as an eco-friendly in contrast to traditional caustic soda scouring in the knit-dyeing factory.